Knowledge on Preconception Care among Bachelor Level Students in a Public Campus of Janakpurdham Sub-Metropolitan City - Gupta, Sunita; Thapaliya, Rekha; Pandey Bista, Archana (Journal of Nursing and Health Sciences Nepal, 2024)
Introduction: Preconception care entails provision of biomedical, behavioral, and social health interventions to women and couples prior to conception aiming to foster a healthy pregnancy and favorable outcomes. The objective of the study was to find out knowledge on preconception care among bachelor level students in a selected public campus of Janakpurdham Sub-Metropolitan City. Methods: A cross-sectional study design was used. Proportionate stratified random sampling method was used to select 209 students studying in different streams of Ram Swaroop Ram Sagar Multiple Campus, Janakpurdham. Structured self-administered questionnaire was used to collect data. Data was analyzed using descriptive statistics (frequency distribution, percentage, means, and standard deviation) to represent the facts and figures and inferential statistics (Chi square test and Fisher’s exact test) to examine the association between the level of knowledge on preconception care and selected variables. Results: The findings of this study revealed that 81.8% of the respondents had inadequate knowledge, 17.7% had moderately adequate and only 0.5% had an adequate level of knowledge on preconception care. There was statistically significant association between the level of knowledge on preconception care and age (p=0.009), sex (p=0.001), educational Stream (p=0.000), genetic problems (p=0.049), and medical problems (p=0.003). Conclusions: It is concluded that most of the students have inadequate knowledge regarding preconception care. Therefore, health education programme and awareness campaigns need to be organized to promote knowledge on preconception care.